2015
DOI: 10.1557/jmr.2015.354
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of VSe2 monolayers separated by bilayers of BiSe

Abstract: The [(BiSe) 11d ] 1 (VSe 2 ) 1 heterostructure was characterized structurally and electrically to determine the effects of interlayer interaction on the charge density wave (CDW) found in VSe 2 and compared to previously reported [(SnSe) 1.15 ] 1 (VSe 2 ) 1 . Out-of-plane x-ray diffraction scans contain reflections that can be indexed as 00l reflections of a BiSe-VSe 2 supercell. Structure refinement indicates that the VSe 2 layer is very similar structurally to that found in [(SnSe) 1.15 ] 1 (VSe 2 ) 1 . Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…The c ‐axis lattice parameters decrease with increasing x until x = 0.50, at which point the repeat unit thickness stays approximately constant with the lattice parameter of the x = 1.0 compound. A previous study of MER‐prepared (Bi x Sn 1– x Se) 1+ δ VSe 2 compounds observed the same trend in c parameter with x , . The total decrease in c ‐axis lattice parameter in the compounds reported here is about 15 pm, the same as that for the VSe 2 ‐containing compounds and the parent end member compounds,, and is likely due to the difference in nominal valence between the Bi(3+) and Sn(2+) cations.…”
Section: Resultssupporting
confidence: 77%
“…The c ‐axis lattice parameters decrease with increasing x until x = 0.50, at which point the repeat unit thickness stays approximately constant with the lattice parameter of the x = 1.0 compound. A previous study of MER‐prepared (Bi x Sn 1– x Se) 1+ δ VSe 2 compounds observed the same trend in c parameter with x , . The total decrease in c ‐axis lattice parameter in the compounds reported here is about 15 pm, the same as that for the VSe 2 ‐containing compounds and the parent end member compounds,, and is likely due to the difference in nominal valence between the Bi(3+) and Sn(2+) cations.…”
Section: Resultssupporting
confidence: 77%
“…It demonstrates that 2H-VSe 2 monolayer could be used in valleytronics well above room temperature. Note that the pristine 1T-phase VSe 2 has been widely studied38394041. However, with the presence of space inversion symmetry, it is definitely not a ferrovalley material.…”
Section: Resultsmentioning
confidence: 99%
“…36 Extrapolation of the linear fit to x = 1 results in a c-axis lattice parameter of 1.172(7) nm, which is smaller but close to the observed value of 1.179 nm for ([BiSe] 1+d ) 1 (VSe 2 ) 1 reported previously. 27 The Bi-content and the (Bi + Sn)/V-ratio together with the corresponding c-axis lattice parameters for each sample are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This approach to indirect doping with electrons might open a new pathway to optimizing the charge density wave transition for specific applications. However, earlier studies on misfit layer compounds 28,29 and ferecrystals 27,30 containing BiX, with X = S or Se, demonstrated that the behavior of Bi within the compounds depends strongly on structural features as well as the transition metal of the dichalcogenide layer, and no general prediction is possible.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation